Kinetic characterization of lactate dehydrogenase in normal and malignant human breast tissues - Talaiezadeh, Abdolhassan (Cancer Cell Int, 2015)
BACKGROUND: Aerobic glycolysis rate is higher in breast cancer tissues than adjacent normal tissues which providethe ATP, lactate and anabolic precursors required for tumourgenesis and metastasis. Lactate dehydrogenase (LDH) is a critical enzyme during aerobic glycolysis as it is typically responsible for the production of lactate and regeneration of NAD(+), which allows for the continued functioning of glycolysis even in the absence of oxygen. LDH has been found to be highly expressed in breast tumors. Enzyme kinetic characteristics is related to environmentinvolving the enzyme, and tumor microenvironment has distinct features relative to adjacent normal tissues, thus we hypothesized that LDH should have different kinetic characteristics in breast tumors compared to normal breast tissues. METHODS: LDH was partially purifiedfrom human breast tumors and normal tissues, which were obtained directly from operating room. TheMichaelis-Menten constant (K(m)), maximum velocity (V(max)), activation energy (E(a)) and enzyme efficiency in breast tumors and normal tissueswere determined. RESULTS: It was found that tumor LDH affinity in forward reaction was the same as normal LDH but V(max) of cancerous LDH was higher relative to normal LDH. In reverse reaction, affinity of tumor LDH for lactate and NAD(+) was lower than normal LDH, also enzyme efficiency for lactate and NAD(+) was higher in normal samples. The E(a) of reverse reaction was higher in cancerous tissues. CONCLUSIONS: It was concluded that thelow LDH affinity for lactate and NAD(+) is a valuable tool for preserving lactate by cancer cells. We also conclude that increasing of LDH affinity may be a valid molecular target to abolish lactate dependent tumor growth and kinetic characteristics of LDH could be a novel diagnostic parameter for human breast cancer.